2012
DOI: 10.1186/1471-2334-12-5
|View full text |Cite
|
Sign up to set email alerts
|

R-848 triggers the expression of TLR7/8 and suppresses HIV replication in monocytes

Abstract: BackgroundToll-like receptors (TLR) 7 and 8 are important in single-stranded viral RNA recognition and may play a role in HIV infection and disease progression. We analyzed TLR7/8 expression and signaling in monocytes from HIV-infected and uninfected subjects to investigate a pathway with new potential for the suppression of HIV replication.MethodsEighty-one HIV-infected and uninfected subjects from Liaoning and Henan provinces in China participated in this study. Monocytes were isolated from subjects' periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 49 publications
3
26
0
Order By: Relevance
“…Hepatitis C virus encodes a non-structural disordered protein, NS5A which impairs TLR2 signalling by targeting MyD88 [69]. Studies with HIV-positive patients showed that the mRNA expression of TLR7/8 decreased during disease progression, and that activation of the TLR7/8 receptors led to suppression of HIV replication in monocytes [72]. In T cells however, HIV causes an upregulation of TLR7 resulting in T-cell anergy [73].…”
Section: Resultsmentioning
confidence: 99%
“…Hepatitis C virus encodes a non-structural disordered protein, NS5A which impairs TLR2 signalling by targeting MyD88 [69]. Studies with HIV-positive patients showed that the mRNA expression of TLR7/8 decreased during disease progression, and that activation of the TLR7/8 receptors led to suppression of HIV replication in monocytes [72]. In T cells however, HIV causes an upregulation of TLR7 resulting in T-cell anergy [73].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, TLR8‐mediated innate immune responses might play a key role in viral pathogenesis. Several clinical studies have demonstrated the antiviral effect of TLR8 in response to ligand stimulation . The ssRNA genome of HCV is a well‐known natural ligand for TLR8 activation .…”
Section: Discussionmentioning
confidence: 99%
“…However, the results showed a lack of adequate efficacy and severe side effects at higher doses [140]. Resiquimod treatment suppressed HIV replication in cultured human monocytes [141]. Another TLR7/8 agonist, CL097, was reported to restore defective cytokine secretion by myeloid DCs of HIV-infected pregnant women and newborns [142].…”
Section: Tlr7/8mentioning
confidence: 99%